1991
DOI: 10.1017/s0022215100115051
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of submandibular duct transposition for drooling

Abstract: This study examines the long-term results and morbidity of submandibular duct transposition in drooling children. Twenty-two patients, aged 3 to 18 years, with neurological dysfunction and excessive drooling underwent submandibular duct transposition between 1984 and 1987. In January 1990, 20 patients were reviewed. Their degree of drooling pre-operatively, immediately post-operatively and currently was assessed. The rate of improvement and the occurrence of complications were noted. Drooling was ‘much better’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In some of the studies, measurement scales was scored by the researcher before and after interventions (Chang & May-Kuen Wong a, 2001;Martin & Conley, 2007), while in another study parents were asked to rate the drooling changes (Burton, Leighton, & Lund, 1991). …”
Section: Studies On Questionnaire-based Scalesmentioning
confidence: 99%
“…In some of the studies, measurement scales was scored by the researcher before and after interventions (Chang & May-Kuen Wong a, 2001;Martin & Conley, 2007), while in another study parents were asked to rate the drooling changes (Burton, Leighton, & Lund, 1991). …”
Section: Studies On Questionnaire-based Scalesmentioning
confidence: 99%
“…However, our evidence can be interpreted to suggest that more-invasive procedures that aggressively target all 4 major salivary glands are perhaps more effective than less-invasive procedures. The trend Puraviappan et al 52 Glynn and O'Dwyer 48 McAloney et al 46 O'Dwyer and Conlon 35 Puckett et al 32 Fear et al 24 Pogrel 23 Brown et al 22 Bailey and Wadsworth 21 Cranin and Bennett 19 Crysdale 20 Cotton and Richardson 17 Morgan et al 18 Massengill 14 Chait and Kessler 11 Guerin 13 Dundas and Peterson 12 Massengill 14 Glass et al 10 Brody 7 Wilkie and Brody 8 Wilkie 4 Martln and Conley 51 Syeda et al 47 Greensmith et al 45 De et al 42 Shirley et al 43 Stern et al 41 Panarese et al 39 Wilson and Henderson 38 Klem and Mair 36 Mankarious et al 37 Becmeur et al 34 Webb et al 33 Varma et al 31 Burton et al 30 Rosen et al 29 O'Dwyer et al 27 Shott et al 28 Crysdale and White 26 Brundage and Moore 25 Hornibrook 49 Uppal et al 44 Crysdale et al …”
Section: Commentmentioning
confidence: 99%
“…Numerous studies have reported SMDR to be effective and well tolerated. [5][6][7][8][9] For obvious reasons, this particular procedure is not suitable for children with a high risk of aspiration (posterior drooling).…”
mentioning
confidence: 99%